ChemInform Abstract: Efficient Visible Driven Photocatalyst, Silver Phosphate: Performance, Understanding and Perspective. Issue 50 (December 2015) - Martin, David James; Liu, Guigao; Moniz, Savio J. A.; Bi, Yingpu; Beale, Andrew M.; Ye, Jinhua; Tang, Junwang
Abstract: Review: 82 refs.